Formulating, packaging, and marketing of natural cosmetic products - Dayan, Nava; Kromidas, Lambros (Wiley, 2011)
"Balanced coverage of natural cosmetics, and what it really means to be "green" The use of natural ingredients and functional botanical compounds in cosmetic products is on the rise. According to industry estimates, sales of natural personal care products have exceeded $7 billion in recent years. Nonetheless, many misconceptions about natural products-for instance, what "green" and "organic" really mean-continue to exist within the industry. Formulating, Packaging, and Marketing of Natural Cosmetic Products addresses this confusion head-on, exploring and detailing the sources, processing, safety, efficacy, stability, and formulation aspects of natural compounds in cosmetic and personal care products. Designed to provide industry professionals and natural product development experts with the essential perspective and market information needed to develop truly "green" cosmetics, the book covers timely issues like biodegradable packaging and the potential microbial risks they present, the use of Nuclear Magnetic Resonance (NMR) to identify biomarkers, and chromatographic methods of analyzing natural products. A must-read for industry insiders, Formulating, Packaging, and Marketing of Natural Cosmetic Products provides the reader with basic tools and concepts to develop naturally derived formulas."--Resumé vydavatele
Keywords: přírodní kosmetické přípravky; natural cosmetics; kolektivní monografie; elektronické knihy; collective monographs; electronic books